Response of Maize to Varying Levels of N, P and K - Pande, R.C.; Rajput, V,S.; Singh, O.P.; Jain, H.C. (Journal of Soil and Water Conservation, 2022)
Maize is an important crop of India, where major area is under rainfed conditions. The average yield of maize in India is 9.1 q. per ha which is very low as compared to 46.3 q. per ha of U.S.A. One of the main causes of low yield in India is the use of low doses of fertilizers, which is 4.97 kg per ha as com- pared to 59.62 kg per ha of U.S.A. Recent experiments and demonstrations conducted all over the country have shown very high yields (195 q. per ha) at high level of agri- cultural efficiency, and even at low level of agricultural efficiency, 74 q. per ha have been obtained (3). Increase in yields, due to the application of N, has been recorded by various workers (13, 2, 4, 11 and 1). Increase in yield, due to the application of P, has been reported (10 and 9). Application of K has been reported (9) to be helpful for increasing the yields of maize.